Siaga Kids: An Educational Game for Enhancing Self-Safety Awareness Among Elementary School Students - Husein Abimanyyu; Chanifah Indah Ratnasari; Septiana Widayanti (bit-Tech, 2025)
Safety education is a crucial component of early childhood learning, as elementary school students often have limited ability to identify potential dangers and respond appropriately. Although numerous studies have introduced educational games for safety learning, most focus on a single topic, such as disaster preparedness or traffic safety. There remains a lack of integrated, multi-threat learning media that simultaneously address different types of risks within one child-friendly platform. This study aims to address this gap by developing "Siaga Kids," an Android-based educational game designed to enhance children’s safety awareness through interactive and age-appropriate gameplay. The development process followed the ADDIE model, which consisted of Analysis, Design, Development, Implementation, and Evaluation. The game covers three key safety themes—earthquake preparedness, traffic sign recognition, and awareness of strangers—presented through visual storytelling and simple, engaging interactions suited for young learners. The study involved 20 students from grades 2 and 3 (ages 7–9) at SDII Nurul Musthofa, Klaten, Indonesia. Data collection included a pre-test, post-test, and a usability evaluation using the System Usability Scale (SUS). The findings show an improvement in students’ average scores from 8.10 to 9.75 after playing the game. The SUS score of 80.71 indicates “Acceptable” usability with an “Excellent” adjective rating. These results demonstrate that "Siaga Kids" is easy to use, engaging, and well-received by young users. Overall, the game effectively supports multi-threat safety education and offers a promising digital tool for strengthening personal safety awareness in elementary school children.